Hydrometallurgical nickel and cobalt productıon from lateritic ores: Optimization and comparison of atmospheric pressure leaching and pug-roast-leaching processes - Çoban, Ozan; Başlayıcı, Serkan; Buğdaycı, Mehmet; Açma, Mahmut Ercan (SciCell s.r.o., 2021)
Corresponding to the technological developments, production and consumption of nickel have increased greatly over time due to its unique mechanical and chemical properties. Therefore, the production of nickel will always keep its importance. The availability of laterite ores, which are oxide type ores, is 86% of the nickel reserves on the Earth, and the processes used in the production of nickel from sulphide type ores have negative environmental effects. Therefore, recovery of nickel from lateritic ores has become increasingly important in recent years. In this study, the aim was to determine the optimum parameters of nickel and cobalt production from limonite type lateritic nickel ores, which were taken from Manisa Caldag region of Turkey, using atmospheric pressure sulfuric acid leaching and pug-roast-leach process. When the results obtained in these processes were compared, it was found that the Ni leaching efficiency is nearly 8% higher and iron leaching efficiency (contamination) is nearly 4% lower in the pug-roastleach process. Furthermore, the pug-roast-leach process was completed in 33% lower time compared to the atmospheric pressure sulfuric acid leaching process.
Keywords: Nickel; Cobalt; Hydrometallurgy; Pug-Roast-Leaching; Atmospheric Pressure